GE_GERICHTE C/14278/2012 vom 24. Juni 2014 - GE Cour de justice (2014)
RESPONSABILITÉ DE DROIT PRIVÉ; RESPONSABILITÉ DU FAIT DES PRODUITS; PRESCRIPTION; PÉREMPTION | LRFP.1; LRFP.9; LRFP.10; CO.55; CO.60